Answer:
[tex]x = -\frac{7 + 2z}{(y + 1)}[/tex]
Step-by-step explanation:
-2z - xy = x + 7
Add 2z to both sides:
-2z + 2z - xy = x + 7 + 2z
-xy = x + 7 + 2z
Next, subtract x from both sides:
-xy - x = x - x + 7 + 2z
- xy - x = 7 + 2z
Factor out -x from the left-hand side of the equation:
- x(y + 1) = 7 + 2z
Divide both sides by - (y + 1) to isolate x:
[tex]\frac{x(y + 1)}{- (y + 1)} = \frac{7 + 2z}{-(y + 1)}[/tex]
[tex]x = -\frac{7 + 2z}{(y + 1)}[/tex]
Please mark my answers as the Brainliest, if you find this helpful :)